Hungarian Monitoring, 15 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev receives Baltic leaders - GDR withdraws invitation to West German social democrat parliamentary delegation - Reports on the Azerbaijani situation - American foodstuffs aid to Poland - Austria extends financial support to Eastern European countries Domestic Affairs: - Mátyás Szűrös's talks in the US - National roundtable talks - Imre Kónya at the Hungarian Democratic Forum (MDF) gathering - Budapest Council's housing policy concept - Hungarian-Vatican diplomatic relations - GDR refugees - Romanian refugees Economy: - National Bank issues ECU bonds - Rockefeller company takes part in formation of joint company in Budapest to explore investment opportunities - World Exposition Külpolitika: - Gorbacsov fogadta a balti vezetőket - Az NDK visszavonta egy nyugatnémet szociáldemokrata parlamenti küldöttség meghívását - Tudósítások az azerbajdzsáni helyzetről - Amerikai élelmiszersegély Lengyelországnak - Ausztria pénzügyi támogatást nyújt a kelet-európai országoknak Belpolitika: - Szűrös Mátyás tárgyalásai az Egyesült Államokban - Nemzeti Kerekasztal tárgyalások - Kónya Imre a MDF összejövetelén - A Fővárosi Tanács lakásgazdálkodási koncepciója - Magyar-vatikáni diplomáciai kapcsolatok - NDK-s menekültek ügye - Romániai menekültek ügye Gazdaság: - ECU-kötvényeket bocsát ki a Nemzeti Bank - A Rockefeller cég részvételével vegyes vállalat alakult Budapesten befektetési lehetőségek feltárására - Világkiállítás